DEEPENING THEORETICAL KNOWLEDGE AND EXPLORING THE PROPERTIES OF LOCAL ANESTHETICS - Martins, Victor Balceiro Legname; Destefani, Afrânio Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
Local anesthetics are indispensable agents in medical practice, offering targeted pain relief while maintaining patient consciousness. Their applications span a wide range of medical fields, including anesthesiology, surgery, and dentistry. Despite their widespread use, the complex pharmacology and potential for adverse effects necessitate a comprehensive understanding of these agents. This narrative review aims to provide an in-depth analysis of the physiology, pharmacology, and clinical applications of local anesthetics. A systematic search was conducted on PubMed, focusing on articles published in English between 2018 and 2023. Local anesthetics have evolved significantly since the first use of cocaine in the late 19th century, with newer derivatives like Lidocaine and Bupivacaine offering improved safety and efficacy. These agents are categorized into aminoesters and aminoamides based on their molecular structure, which also influences their pharmacokinetics and pharmacodynamics. The primary mechanism of action involves the modulation of voltage-gated sodium channels, although the complete mechanism remains an area of active research. Various factors, including lipid solubility, plasma pH, and pKa, influence the drug's onset, duration, and potential for toxicity. Adjuvants like adrenaline can enhance the drug's properties. Local anesthetics are a cornerstone in modern medicine, offering targeted anesthesia with a relatively favorable safety profile. Understanding their complex pharmacology is crucial for optimizing their clinical use. Future research should focus on elucidating the complete mechanisms of action and exploring the potential for new adjuvants to improve efficacy and safety.